2023
DOI: 10.3390/life13010185
|View full text |Cite
|
Sign up to set email alerts
|

Direct Mechanical Thrombectomy Versus Prior Bridging Intravenous Thrombolysis in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: The current guideline recommends using an intravenous tissue-type plasminogen activator (IV tPA) prior to mechanical thrombectomy (MT) in eligible acute ischemic stroke (AIS) with emergent large vessel occlusion (ELVO). Some recent studies found no significant differences in the long-term functional outcomes between bridging therapy (BT, i.e., IV tPA prior to MT) and direct MT (dMT). Methods: We conducted a systematic review and meta-analysis to compare the safety and functional outcomes between BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 90 publications
(158 reference statements)
1
6
0
Order By: Relevance
“… 32 Kolahchi et al , when analyzing 4 RCTs and 9 observational studies, found no differences regarding functional independence and mortality, but reported higher rates of sICH in the BT group (OR 0.73; 95 % CI, 0.56–0.96, p = 0.02, I 2 = 0 %), a result that remained significant only in the observational studies group after subgroup analysis; likewise, successful reperfusion rate was higher for BT in the RCTs subgroup (OR 0.73; 95 % CI, 0.56–0.96, p = 0.02, I 2 = 0 %).). 22 The overall results of this study differ from ours in the pooled analysis; however, the RCTs subgroup analysis is consistent with ours. We believe that the main limitation of these publications is that they have a high risk of bias due to the combination of different methodological designs and analysis, which would explain their high heterogeneity; 33 therefore, it is more appropriate to use data provided only from randomized clinical trials to guide clinical practice on the topic.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“… 32 Kolahchi et al , when analyzing 4 RCTs and 9 observational studies, found no differences regarding functional independence and mortality, but reported higher rates of sICH in the BT group (OR 0.73; 95 % CI, 0.56–0.96, p = 0.02, I 2 = 0 %), a result that remained significant only in the observational studies group after subgroup analysis; likewise, successful reperfusion rate was higher for BT in the RCTs subgroup (OR 0.73; 95 % CI, 0.56–0.96, p = 0.02, I 2 = 0 %).). 22 The overall results of this study differ from ours in the pooled analysis; however, the RCTs subgroup analysis is consistent with ours. We believe that the main limitation of these publications is that they have a high risk of bias due to the combination of different methodological designs and analysis, which would explain their high heterogeneity; 33 therefore, it is more appropriate to use data provided only from randomized clinical trials to guide clinical practice on the topic.…”
Section: Discussionsupporting
confidence: 79%
“…Recent clinical trials, observational studies, as well as pooled data and meta-analyses, suggest that direct mechanical thrombectomy (dMT) could be as effective as bridging therapy (BT), obtaining good functional results on its own. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 In clinical practice, IVT prior to MT (BT) has potential benefits and risks. Although some studies suggested that IVT may increase the perfusion of large occluded vessels and improve the general outcome, the recanalization rate is relatively low, especially in proximal vessel occlusions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review and meta-analysis comparing BT and direct MT for AIS with LVO found no significant difference in mortality and functional outcome after 90 days. 95 As per Indian guidelines, AIS patients with LVO may be considered for bridging IV thrombolysis (alteplase 0.9 mg/kg infusion or Tenecteplase 0.2-0.25 mg/kg bolus) followed by MT. 96 In India, MT costs approximately 400,000-500,000 INR.…”
Section: Lvos and Mtmentioning
confidence: 99%